Factors Affecting Tourists' Revisit Decision: A Quantitative Analysis: Pengaruh Faktor-faktor terhadap Keputusan Wisatawan untuk Kembali: Analisis Kuantitatif - Abdul Kodir; Asat Rizal (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative research study aimed to investigate the impact of travel attraction, facility, price, and accessibility on tourists' decision to revisit Banyubiru Pasuruan. The sample comprised 95 visitors to Banyubiru Pasuruan, and path analysis using SPSS software version 18.00 was employed as the analytical tool. The findings revealed that travel attraction, facility, price, and accessibility individually exerted a partial influence on the decision to revisit, while collectively, they significantly affected tourists' decision to revisit Banyubiru Pasuruan. These results contribute to the understanding of the factors influencing tourists' decision-making process and have important implications for destination management and marketing strategies aimed at enhancing visitor satisfaction and fostering repeat visits. Highlights: Factors influencing tourist decision: Explore the key factors that impact tourists' decision to revisit Banyubiru Pasuruan. Quantitative analysis: Employ a rigorous quantitative approach to examine the relationships between travel attraction, facility, price, accessibility, and tourist revisit decision. Implications for destination management: Provide valuable insights for destination managers to enhance visitor satisfaction and develop effective marketing strategies for encouraging repeat visits to Banyubiru Pasuruan. Keywords: Tourist decision, Revisit, Quantitative analysis, Factors, destination